Whose river is it?: an assessment of livelihood and cultural water flow requirements for the Karnali Basin - Sharma, Akriti; Karki, Emma; Eriyagama, Nishadi; Shrestha, Gitta; Jeuland, Marc; Bharati, Luna (Resilience Alliance, Inc., 2020)
The term “environmental flows” refers to a combination of features, including quantity, quality, and timing of water flows required to sustainably maintain a river’s health, balancing both ecological and societal needs. Incorporating basic human livelihood and sociocultural aspects in environmental flow assessments alongside ecological concerns provides a more holistic perspective on water flow management. Here, we provide an assessment that complements an ecosystem functioning lens by focusing solely on quantifying the flows associated with livelihood activities and spiritual water requirements of local riparian communities in the Karnali basin in Western Nepal. This assessment is based on the first social survey related to environmental flows conducted in the Karnali basin. We collected data using mixed methods, including social surveys, key informant interviews, and focus group discussions, across six locations in the Karnali basin that provide us with a rich and dynamic perspective on the relationship between rivers and their surrounding communities, and the challenges faced by those communities. Among the subsistence and spiritual requirements of local communities are uses for activities that include drinking, small-scale irrigation, domestic needs, fishing, and ceremonial usage. All communities we visited most strongly associated the following activities with water flow variation: small-scale irrigation, fishing, ceremonial usage, domestic needs, and tourism. The water flows required for these key activities were quantified, and results from the six sites are presented in the form of a qualitative scale of minimum water levels (ranging across poor, acceptable, and ideal) required to meet vital local needs. The minimum acceptable water flow requirement to satisfy social criteria is just > 20% of the mean annual runoff at the visited locations. These requirements are particularly vital to consider, given ongoing efforts to tap the vast hydropower potential in Nepal through construction of major storage projects. Such projects would change the flow regime of affected rivers and potentially raise concerns that existing demands might be compromised.